The Impact of Childhood Trauma on Developing Bipolar Disorder: Current Understanding and Ensuring Continued Progress - Quidé Y (Dove Medical Press, 2020)
Yann Quidé,1,2 Leonardo Tozzi,3 Mark Corcoran,4 Dara M Cannon,5 Maria R Dauvermann6,7 1School of Psychiatry, University of New South Wales (UNSW), Sydney, NSW, Australia; 2Neuroscience Research Australia, Randwick, NSW, Australia; 3Department of Psychiatry and Behavioral Sciences, Stanford University, Stanford, CA, USA; 4School of Psychology, National University of Ireland Galway, Galway, Ireland; 5Centre for Neuroimaging & Cognitive Genomics (NICOG), Clinical Neuroimaging Laboratory, NCBES Galway Neuroscience Centre, School of Medicine, National University of Ireland Galway, Galway, Ireland; 6Department of Psychiatry, University of Cambridge, Cambridge, UK; 7McGovern Institute for Brain Research, Massachusetts Institute of Technology, Cambridge, MA, USACorrespondence: Maria R DauvermannDepartment of Psychiatry, University of Cambridge, Clifford Allbutt Building, Cambridge Biomedical Campus Box 58, Cambridge CB2 0XY, UKTel +441223 465246Email md874@medschl.cam.ac.ukAbstract: Childhood trauma (CT) has been repeatedly linked to earlier onset and greater severity of bipolar disorder (BD) in adulthood. However, such knowledge is mostly based on retrospective and cross-sectional studies in adults with BD. The first objective of this selective review is to characterize the short-term effects of CT in the development of BD by focusing on studies in young people. The second objective is to describe the longer-term consequences of CT by considering studies with adult participants. This review first outlines the most prominent hypotheses linking CT exposure and the onset of BD. Then, it summarizes the psychological and biological risk factors implicated in the development of BD, followed by a discussion of original studies that investigated the role of CT in young people with early-onset BD, youths at increased risk of developing BD, or young people with BD with a focus on subclinical and clinical outcome measures. The review considers additional biological and psychological factors associated with a negative impact of CT on the long-term course of BD in later adulthood. Finally, we discuss how the integration of information of CT can improve ongoing early identification of BD and mitigate severe clinical expression in later adulthood.Keywords: bipolar disorder, childhood trauma, vulnerability, early onset, peripheral blood marker, brain